Assessing willingness to pay for safe drinking water in Tala union of Satkhira district, Bangladesh (BRAC University Journal, 2026)
The people of the coastal regioo of Bangladesh are facing severe difficulties in accessing safe drinking water mainly during the dry period. Tala upazila of Satkhira district is ooe of the most affected areas because of widespread arsenic contamination in shallow aquifer, salinity in ground and surface water, difficulties in extractiog saline free aquifer due to hard rocks/stooes and excessive iron. There is an acute shortage of safe drinking water in the villages of Tala mainly due to low accessibility and inadequate quality of drinking water. This paper has been extracted from the pilot study cooducted in Tala union in 2015 to identify local people's preference for drinking water sources, their preferred option for buying and willingoess to pay for access to safe drinking water as well as to find out the opportunity of existiog water selling business. Water pricing, as one of the most iroportant element to develop water selling business model, requires the information regarding the willingoess to pay and affordability of the users for access to safe drinking water. This paper focuses on the willingoess of the households of Tala to pay for safe drinking water according to socio-ecooomic class of the households. Data required to determine willingoess of the households to pay was collected from survey, FGD and Kll. All the households in Tala Union, 8613 in total was covered in the household census. The household census dsta revealed that the pipe water supply to households was the most preferred option by the local people for buying drinking water. However, a large percentage of households were willing to buy drinking water either from any specific place or if water is supplied to their house in gallons. On an average 60% of the households were willing to pay for access to safe drinking water. Most of the respondents were ready to spend Tk. 20 per week to buy safe drinking water. The positive respouse for willingoess to pay for safe drinking water was fouod higher amongst the non-poor respondent (71%) as opposed to the poor (58%) and the ultra-poor (48%). So it is pre!rY obvious that socioeconomic status has an effect oo household's willingoess to pay for safe drinking water. Households of different socio-economic class were willing to pay 3% to 6% of their respective monthly income to access safe drinking water. As most of the households are willing to pay for buying drinking water, entrepreneurship development for water selling business can be encouraged to supply safe drinking water with minimum cost; thus eroployment of scme local people as well as ensuring access to safe drinking water can be achieved at the same time. At the same time, the water selling business, which has already started in Tala, should be given more importance and its promotion, proper manageroent, technical support and supervision should be prioritized to ensure its sustainable growth.